Patellar osteochondral involvement in chondromalacia patella: An exploratory routine MRI-based three-tier framework - Karaagac, Seda Sogukpinar; Capkur, Firdevs (Elsevier Science Inc, 2026)
Purpose To preliminarily evaluate whether routine knee MRI demonstrates reproducible patterns of combined patellar cartilage and subchondral bone involvement using an exploratory three-tier patella-focused osteochondral MRI framework. Methods This retrospective single-center lesion-based study included 200 knee MRI examinations performed between January 1, 2024 and January 1, 2026. Patellar cartilage damage was graded as Amax (0-4), and subchondral bone abnormalities were graded as Bmax (0-3). Examinations were categorized as Tier 1 low-burden involvement, Tier 2 discordant involvement, or Tier 3 concordant advanced involvement. Field-strength subgroup analyses were performed to assess potential differences between 1.5-T and 3-T examinations. Results Interobserver agreement was high for Amax (weighted kappa = 0.82) and Bmax (weighted kappa = 0.85), and excellent for the composite score (ICC = 0.91). Cartilage and bone grades were positively correlated (Spearman's rho = 0.637, p < 0.001). Tier 1, Tier 2, and Tier 3 patterns were observed in 43.5%, 23.5%, and 33.0% of examinations, respectively. Within Tier 2, cartilage-predominant and bone-predominant patterns accounted for 38/47 (80.9%) and 9/47 (19.1%) cases, respectively. Field-strength analysis showed a difference in detailed Amax grade distribution (p = 0.021), whereas high-grade cartilage involvement, Bmax distribution, framework category, and composite score did not differ significantly between 1.5-T and 3-T examinations. Conclusion Routine knee MRI may reveal low-burden, discordant, and concordant advanced patterns of patellar osteochondral involvement. The proposed framework provides an exploratory structural description of combined cartilage-bone involvement rather than a validated staging system or a proven replacement for conventional grading.
Keywords: Chondromalacia Patella; Patella; Bone Marrow Lesion; Magnetic Resonance Imaging; Osteochondral Phenotype